Describing the Challenges of Prehospital Rapid Sequence Intubation by Macintosh Blade Video Laryngoscopy Recordings. Issue 4 (3rd August 2022) - Hayes-Bradley, Clare; Gemal, Hugo; Miller, Matthew; Ware, Sandra
Abstract: Study Objective: Structured review of video laryngoscopy recordings from physician team prehospital rapid sequence intubations (RSIs) may provide new insights into why prehospital intubations are difficult. The aim was to use laryngoscope video recordings to give information on timings, observed features of the airway, laryngoscopy technique, and laryngoscope performance. This was to both describe prehospital airways and to investigate which factors were associated with increased time taken to intubate. Methods: Sydney Helicopter Emergency Medical Service (HEMS; the aeromedical wing of New South Wales Ambulance, Australia) has a database recording all intubations. The database comprises free-text case detail, airway dataset, scanned case sheet, and uploaded laryngoscope video. The teams of critical care paramedic and doctor use protocol-led intubations with a C-MAC Macintosh size four laryngoscope and intubation adjunct. First-pass intubation rate is approximately 97%. Available video recordings and their database entries were retrospectively analyzed for pre-specified qualitative and quantitative factors. Results: Prehospital RSI video recordings were available for 385 cases from January 2018 through July 2020. Timings revealed a median of 58 seconds of apnea from laryngoscope entering mouth to ventilations. Median time to intubate (laryngoscope passing lips until tracheal tube inserted) was 35 seconds, interquartile range 28-46 seconds. Suction was required prior to intubation in 29% of prehospital RSIs. Fogging of the camera lens at time of laryngoscopy occurred in 28%. Logistic regression revealed longer time to intubate was associated with airway soiling, Cormack-Lehane Grade 2 or 3, multiple bougie passes, or change of bougie. Conclusion: Video recordings averaging 35 seconds for first-pass success prehospital RSI with an adjunct give bed-side "definitions of difficulty" of 30 seconds for no glottic view, 45 seconds for no bougie placement, and 60 seconds for no endotracheal tube placement. Awareness of apnea duration can help guide decision making for oxygenation. All emergency intubators need to be cognizant of the need for suctioning. Improving the management of bloodied airways and bougie usage may reduce laryngoscopy duration and be a focus for training. Video screen fogging and missed recordings from some patients may be something manufacturers can address in the future.